Capital Access Disparities Among Migrant Workers: Evidence from Informal Sector - Wildan Syafitri; Axellina Muara Setyanti; Nila Cahayati (Economics Development Analysis Journal, 2025)
This research investigates the dynamics of working capital access among migrant workers in Indonesia's informal sector, aiming to identify key factors influencing capital access and the challenges this group faces. Utilizing data from the Survei Sosial Ekonomi Nasional (SUSENAS), this study employs a logistic regression model to examine various determinants of access to financial capital. The findings indicate that higher education increases access to commercial banks and Bank Perkreditan Rakyat (BPR) loans but reduces access to Kredit Usaha Rakyat (KUR) and cooperative credit. Digital literacy, reflected by internet usage, enhances access to KUR and BPR loans, although it does not influence cooperative credit. Younger and married individuals are more likely to obtain credit, while urban residents are more likely to access commercial bank and BPR loans but face limitations with KUR and cooperative credit. These results underscore the need for tailored financial inclusion strategies that address the specific needs of different demographic and geographic groups. Improving digital literacy and developing customized financial products for migrant informal workers may enhance their financial inclusion and access to working capital.